The Halodoc’s Social Media Data Analysis Amidst Covid-19 Pandemic: An Evidence from Indonesia - Hilarius Bambang Winarko; Diana Intan Pratiwi; Linda MacGrain Herkenhoff (Jurnal Sosial Humaniora, 2023)
This study aims to analyze Halodoc telehealth services reputation through itssocial media during Covid-19 pandemic critical time of 2020-2021 by usingbig data analysis. During that period, more people increasingly used e-healthapplication services. This study applies data scraping technique to analyze bigdata collected from Halodoc’s social media official accounts. The analysisincludes contents, views, comments, likes, dislikes, and shares from theaudiences toward Halodoc’s social media platforms. The results indicate thatHalodoc’s brand reputation is considered positive. YouTube was theHalodoc’s social media platform that most got attention from customers’actions (views, likes, comments, and dislikes). Meanwhile, its Instagram wasthe most demanded by customers because they wanted to win the prizes fromHalodoc. And finally, Facebook was the less communicative social mediaplatform, due to the problem on handling the Covid-19 tests. Several issuesneed to be resolved by Halodoc to further meet the user experience’sexpectations.